LAW ENFORCEMENT OF ELECTRICAL AND ELECTRONIC WASTE SMUGGLING IN BATAM, INDONESIA - FX.Joko Priyono (Fakultas Hukum, Universitas Diponegoro, 2017)
Electrical and electronic waste (e-waste) are dangerous for human health and environment. The e-waste may comes from both external (import) and domestic industries. Batam as part of Indonesia jurisdiction have been a place of e-waste dumping. The e-waste mostly comes from Singapore. The rest is from Malaysia, Thailand, and Vietnam. The influx of electronic waste is done through smuggling at certain place. Police actually knows about the smuggling but not take any action. This crimes was backed up by any army and police. It reflects the ineffectiveness of law enforcement in Batam regarding e-waste smuggling. The ignorance causes the environment and human health is not well protected. Lack of understanding of legal knowledge by law enforcement agencies should be a particular concern for the government. On the other hand, for the people of Batam, e-waste still have economic value. Therefore, they don’t care about the menace of e-waste to human health and environment. The government should develop them in order to manage e-waste properly. The government may refer to the Government of India's Bangalore city with regard to how the people manage e-waste.